Generation Z's Trust in Mainstream Media and Social Media in Indonesia and Lebanon - Emeraldien, Fikry; Youssef Harb; Tiara Nauralita; Cindy Melania Fitriani; Alfina Nurhayati (Jurnal Komunikasi Islam, 2024)
This study investigates Generation Z's trust in mainstream and social media in Indonesia and Lebanon. Using a descriptive research design and survey method, data were collected from 114 respondents through Google Forms in April 2022, including students from Universitas Islam Negeri Sunan Ampel (UINSA) Surabaya and participants from @iCademy in Lebanon. The research explores the critical role of mainstream media in modern information dissemination and social media as a powerful communication tool. The results indicate that while social media is widely used, mainstream media maintains credibility due to its verified information. The findings emphasize the importance of reliable information sources for Generation Z, especially in predominantly Muslim contexts where ethical standards and factual accuracy are crucial. These findings suggest that media organizations must uphold high journalistic standards to retain the trust of young audiences.